The effect of different pressures of pneumoperitoneum on the optic nerve sheath diameter – A prospective study - Supraja Ponduru; Ananya Nanda; Vandana Patilbuwa Pakhare; Ramchandran Gopinath; Kalyani Suryadhanalakshmi Sangineni; R Devi Sai Priyanka (The Indian Anaesthetists' Forum, 2023)
Background and Aims: Increased intra-abdominal pressure (IAP) and carbon dioxide gas during pneumoperitoneum leads to various systemic changes involving cardiovascular, respiratory, and cerebral physiology. In our study, we aimed to investigate the effect of standard (13–15 mmHg) and low (6–8 mmHg) pressure pneumoperitoneum on optic nerve sheath diameter (ONSD) using ultrasound, which is a reflection of intracranial pressure (ICP). Patient hemodynamics, surgery duration and surgeons' comfort, and ease of performing surgery at low-pressure pneumoperitoneum were studied as secondary objectives. Materials and Methods: In this prospective double-blind randomized study, 75 patients of the American Society of Anesthesiologists physical status grades I and II, of both genders undergoing elective laparoscopic surgery, were allocated into two groups – S (standard IAP 13–15 mmHg) and L (low IAP 6–8 mmHg). ONSD acquired at different time points: before induction of anesthesia (T1), 5 min after intubation (T2), 5 min after the creation of pneumoperitoneum (T3), 5 min before desufflation (T4), and 5 min before extubation (T5). ONSD of 5 mm is taken as the cutoff value to correlate raised ICP. Continuous variables were analyzed by the Student's t-test, and categorical data were assessed by the Chi-square test. Results: There was a significant increase in ONSD with insufflation in both the groups; however, T3 is higher than the cutoff value (>5 mm) in Group S. The ONSD values at T1 (baseline) and at T2 (after intubation) were comparable between the groups, with P = 0.1855 and P = 0.8988, respectively. With pneumoperitoneum, the increase in ONSD (T3) is significantly higher in Group S than in Group L with P = 0.0022, attributing to the high IAP in Group S. Conclusion: Laparoscopic surgery with low-pressure pneumoperitoneum can be a safe approach, particularly in individuals at risk of raised ICP.